2017
DOI: 10.1016/j.solmat.2017.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Metal nano-grids for transparent conduction in solar cells

Abstract: 2017-08-25T16:29:28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 157 publications
0
26
0
Order By: Relevance
“…[83] Furthermore it has been demonstrated that the discontinuous character of the electrode induces an increase in resistance in the neighboring semiconducting layer, which is why different criteria than the commonly used FoM should be considered for the evaluation of metal grid electrodes. [84] Upon optimization of the pattern dimensions, films with a sheet resistance between 5 Ohm sq -1 to 24 Ohm sq -1 with 70% to 80% transmittance (FoM between 60 and 190) in the visible range can be obtained. [85][86][87] Photovoltaic cells based on such metal grid electrodes exhibited the same performance as ITO reference cells.…”
Section: Metal Gridsmentioning
confidence: 99%
“…[83] Furthermore it has been demonstrated that the discontinuous character of the electrode induces an increase in resistance in the neighboring semiconducting layer, which is why different criteria than the commonly used FoM should be considered for the evaluation of metal grid electrodes. [84] Upon optimization of the pattern dimensions, films with a sheet resistance between 5 Ohm sq -1 to 24 Ohm sq -1 with 70% to 80% transmittance (FoM between 60 and 190) in the visible range can be obtained. [85][86][87] Photovoltaic cells based on such metal grid electrodes exhibited the same performance as ITO reference cells.…”
Section: Metal Gridsmentioning
confidence: 99%
“…Although previously many different semitransparent contact structures have been proposed, [ 15 ] within this work, we focused on hexagonal silver contacts because they have been used widely in organic electronics due to their ability to geometrically pack efficiently. The substrate used for the fabrication process was a 125 μm‐thick polyethylene terephthalate (PET) roll (Melinex 506) purchased from DuPont Teijin Films.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, previous work has shown that lumping series resistance externally yields an exact, explicit equation for TCE merit. [ 5–7 ] For example, a uniform TCE applied to a solar cell operating at its MP point with current density ( J MP ) and voltage ( V MP ) would reduce its current and voltage to J MP,TCE and V MP,TCE JMP,TCEbadbreak=JMPgoodbreak⋅TTCE,avg\[ \begin{array}{*{20}{c}}{{J_{{\rm{MP,TCE}}}} = {J_{{\rm{MP}}}} \cdot {T_{{\rm{TCE,avg}}}}}\end{array} \] VMP,TCEbadbreak=VMPgoodbreak−RTCEgoodbreak⋅Agoodbreak⋅JMPgoodbreak=VMPgoodbreak−Rsh,TCEL2JMP3\[ \begin{array}{*{20}{c}}{{V_{{\rm{MP,TCE}}}} = {V_{{\rm{MP}}}} - {R_{{\rm{TCE}}}} \cdot A \cdot {J_{{\rm{MP}}}} = {V_{{\rm{MP}}}} - \frac{{{R_{{\rm{sh,TCE}}}} \cdot {L^2} \cdot {J_{{\rm{MP}}}}}}{3}}\end{array} \] …”
Section: Where To Lump Series Resistancementioning
confidence: 99%
“…[ 1,14 ] However, metal grids have nonuniformity that induces resistance in the underlying semiconductor, so their merit deviates from that of uniform TCEs. [ 6 ] Therefore, coupling a uniform TCE with a metal grid changes TCE merit. For example, the metal grating in Figure 1c has a transmittance of T grid = s /( s + w ), and the sheet resistance of a grating with ρ metal resistivity and h metal height is R sh,grid = ρ metal · ( s + w )/( w · h metal ).…”
Section: Tce Merit Is Not Universal Because It Depends On Module Arch...mentioning
confidence: 99%
See 1 more Smart Citation